Rapid Detection of High-Level Tigecycline Resistance in Tet(X)-Producing Escherichia coli and Acinetobacter spp. Based on MALDI-TOF MS - Cui, Ze-Hua; Zheng, Zi-Jian; Tang, Tian; Zhong, Zi-Xing; Cui, Chao-Yue; Lian, Xin-Lei; Fang, Liang-Xing; He, Qian; Wang, Xi-Ran; Chen, Chong; He, Bing; Wang, Min-Ge; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
The emergence and spread of the novel mobile Tet(X) tetracycline destructases confer high-level tigecycline and eravacycline resistance in Escherichia coli and Acinetobacter spp. and pose serious threats to human and animal health. Therefore, a rapid and robust Tet(X) detection assay was urgently needed to monitor the dissemination of tigecycline resistance. We developed a rapid and simple assay to detect Tet(X) producers in Gram-negative bacteria based on matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS). This MALDITet(X) test was based on the inactivation of tigecycline by a Tet(X)-producing strain after a 3-h incubation of bacterial cultures with tigecycline. Culture supernatants were analyzed using MALDI-TOF MS to identify peaks corresponding to tigecycline (586 ± 0.2 m/z) and a tigecycline metabolite (602 ± 0.2 m/z). The results were calculated using the MS ratio [metabolite/(metabolite + tigecycline)]. The sensitivity of the MALDITet(X) test with all 216 test strains was 99.19%, and specificity was 100%. The test can be completed within 3 h. Overall, the MALDITet(X) test is an accurate, rapid, cost-effective method for the detection of Tet(X)-producing E. coli and Acinetobacter spp. by determining the unique peak of an oxygen-modified derivative of tigecycline.